Faktor-Faktor yang Mempengaruhi Kualitas Sumber Daya Manusia (SDM) di Kabupaten Siak - Winda, Minar; Maulida, Yusni; Sari, Lapeti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study to analize the factors that affect the quality of human resourcesin Siak District, which of life expectancy, literacy rates, average length of school and average real per capita output adjusted. Analysis of the data used is quantitative method with SPSS (Statistical Package of Social Science) version 21.00. The results os test performed using multiple linear regression analysis, it is known that adjusted 100%. This shows all four independent variables influence on the quality of human resources in Siak District. Simultaneous regression test showed that all independent variables in the examined had a significant effect on the quality of human resources in Siak District. The results of the testing partial regression (t-test) showing that variable of life expectancy, literacy rates, average length of school and average real per capita output adjusted significant effect the human development index. Variables that influence the quality of human resources in Siak District is an average of the real per capita output in adjusted.Keywords : human development index.